English Lecturer's Attitude Toward English Variety In English Learning - Rahma Yanti; Handoko Handoko; Rabbi Antaridha (Masyarakat Linguistik Indonesia Universitas Andalas, 2018)
This research investigates English lecturers' attitude toward the variation of English in the process of English learning. The purpose of this study is to discuss the types of English variations uttered by English lecturers who are considered as respondents in this study and their attitudes toward the variations of language that appear to their own speech during the teaching-learning process. This research is descriptive by using qualitative approach. The data to be presented in this research is taken from several words of Indonesian lecturers at several universities in Padang West Sumatra by distributing some questionnaires and also interviews. The method of data analysis is divided into two types, first, methods which related to the correlation of external language objects with a non-linguistic element called correlation method or method of matching, and secondly, methods which related to surgical, processing or internal verbal tampering called the method of operation or distribution method.